THE ROLE OF THE FAMILY IN IMPROVING THE QUALITY OF PRIMARY EDUCATION - Nagmetova Nursulu Muratbaevna (Galaxy International Interdisciplinary Research Journal, 2021)
In today’s evolving world, the concepts of family and children are becoming more and more abstract. Parents are not allocating enough time for their children. As a result, children develop a variety of bad habits and habits. This article provides some practical and theoretical advice on the role of parents in child-rearing.